2012
DOI: 10.3390/sym4030452
|View full text |Cite
|
Sign up to set email alerts
|

Supersymmetric Quantum Mechanics and Solvable Models

Abstract: Abstract:We review solvable models within the framework of supersymmetric quantum mechanics (SUSYQM). In SUSYQM, the shape invariance condition insures solvability of quantum mechanical problems. We review shape invariance and its connection to a consequent potential algebra. The additive shape invariance condition is specified by a difference-differential equation; we show that this equation is equivalent to an infinite set of partial differential equations. Solving these equations, we show that the known lis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
61
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(64 citation statements)
references
References 41 publications
3
61
0
Order By: Relevance
“…Since the aforementioned zero modes play a crucial role towards the formulation of the quantum theory of supersymmetric Chern-Simons vortices, in this paper we shall present an interesting property of the zero modes of models with global N = 2 spacetime supersymmetry. Particularly, we find that the zero modes of fermionic and bosonic fluctuations of Abelian gauge models having a global N = 2 spacetime supersymmetry in (2 + 1)-dimensions, can separately constitute two N = 2, d = 1 supersymmetric quantum algebras [15][16][17][18][19][20][21][22], with the zero modes being the corresponding quantum Hilbert space vectors. Moreover, due to the N = 2 global spacetime supersymmetry of the theory, the underlying one dimensional N = 2 supersymmetric quantum algebras can form a centrally extended N = 4, d = 1 supersymmetric quantum algebra.…”
Section: Introductionmentioning
confidence: 99%
“…Since the aforementioned zero modes play a crucial role towards the formulation of the quantum theory of supersymmetric Chern-Simons vortices, in this paper we shall present an interesting property of the zero modes of models with global N = 2 spacetime supersymmetry. Particularly, we find that the zero modes of fermionic and bosonic fluctuations of Abelian gauge models having a global N = 2 spacetime supersymmetry in (2 + 1)-dimensions, can separately constitute two N = 2, d = 1 supersymmetric quantum algebras [15][16][17][18][19][20][21][22], with the zero modes being the corresponding quantum Hilbert space vectors. Moreover, due to the N = 2 global spacetime supersymmetry of the theory, the underlying one dimensional N = 2 supersymmetric quantum algebras can form a centrally extended N = 4, d = 1 supersymmetric quantum algebra.…”
Section: Introductionmentioning
confidence: 99%
“…In Ref. [4,5], the authors showed that these superpotentials obey an infinite set of PDEs. In this section, we will describe how to generate these shape invariant systems from the PDEs.…”
Section: Shape Invariant Superpotentialsmentioning
confidence: 99%
“…Since Eq. (3) must hold for an arbitrary value of , we can expand the equation in powers of , and require that the coefficient of each power vanishes, leading to the following two independent equations [4,5] :…”
Section: A Conventional Superpotentialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Arai [5] demonstrated a class of supersymmetric quantum mechanics whose eigenvalues problem has a solvable spectrum. Similarly, in a review paper, Bougie et al [6] presented solvable models within the SUSYQM framework. The authors prove that shape of invariance conditions allows to solve analytically many quantum systems.…”
Section: Introductionmentioning
confidence: 96%